Coplanar Pt/C Nanomeshes with Ultrastable Oxygen Reduction Performance in Fuel Cells. (8th February 2021) - Hu, Yanmin; Zhu, Mengzhao; Luo, Xuan; Wu, Geng; Chao, Tingting; Qu, Yunteng; Zhou, Fangyao; Sun, Rongbo; Han, Xiao; Li, Hai; Jiang, Bin; Wu, Yuen; et al.
Abstract: Developing highly stable and efficient catalysts toward the oxygen reduction reaction is important for the long‐term operation in proton exchange membrane fuel cells. Reported herein is a facile synthesis of two‐dimensional coplanar Pt‐carbon nanomeshes (NMs) that are composed of highly distorted Pt networks (neck width of 2.05±0.72 nm) and carbon. X‐ray absorption fine structure spectroscopy demonstrated the metallic state of Pt in the coplanar Pt/C NMs. Fuel cell tests verified the excellent activity of the coplanar Pt/C NM catalyst with the peak power density of 1.21 W cm −2 and current density of 0.360 A cm −2 at 0.80 V in the H2 /O2 cell. Moreover, the coplanar Pt/C NM electrocatalysts showed superior stability against aggregation, with NM structures preserved intact for a long‐term operation of over 30 000 cycles for electrode measurement, and the working voltage loss was negligible after 120 h in the H2 /O2 single cell operation. Density‐functional theory analysis indicates the increased vacancy formation energy of Pt atoms for coplanar Pt/C NMs, restraining the tendency of Pt dissolution and aggregation. Abstract : A facile synthesis of two‐dimensional coplanar Pt‐carbon nanomeshes with high surface distortion has been developed. This electrocatalyst showed superior activity and stability for the oxygen reduction reaction in a fuel cell.